A Study of the Indonesian Translation of '花 (Huā)' in Polysemous Words from a Cognitive Perspective - Die, Chen; Syaifullah, Aceng Ruhendi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
This study analyzes the polysemy phenomenon of the word